Financial Ratio Analysis to Measure the Financial Performance of the Regional Government of North Sumatera Province for the 2018-2022 Budget Year - Habiba, Habiba; Pitria, Melani; Safitri, Rahma Aliya; Lubis, Yunita br; Chrisna, Heriyati (Jurnal Riset Ilmu Pendidikan, 2024)
This study aims to analyze the financial performance of the North Sumatera Provincial Government using financial ratios as a measuring tool during the 2018-2022 fiscal year period. The financial ratios used in this study include the independence ratio, effectiveness ratio, decentralization ratio, and regional revenue and expenditure growth ratio. The data used were obtained from the annual financial report of the North Sumatera Provincial Government during the period. The analytical method applied is quantitative descriptive analysis, where financial data is processed and analyzed to determine the extent of the regional government's financial performance in budget management and achieving revenue and expenditure targets. The results of the study show that although there are several indicators that show improved performance, several financial ratios still show imbalances that require further attention to improve budget management and strengthen regional fiscal independence. This study is expected to provide a clear picture of the financial condition of the regional government and provide recommendations for improvements in regional financial management in the future.